"Preparing Secondary Effluent for Urban Non- Potable Applications by Floating Media Filtration" - F Vaezi; AH Mahvi; G Safari (Tehran University of Medical Sciences, 2003)
Conventional sand filtration which has become a common wastewater treatment technology to satisfy regulations appointed for effluent reuse, suffers from the disadvantage of high energy for backwashing. The subject of this study is application of downflow floating media prior to coarse sand filtration, which requires less water for backwash. Two pilots have been employed in two stages. For the first stage, a pilot of two columns was used, one was packed with plastic beads and the other with coarse sand. For the second, floating medium was placed on the sand in a unique column. The effluent of Ghods Treatment Plant was selected as the influent for the both pilots and a turbidity of 2NTU for the filter effluent has been specified as the breakthrough. Final results showed the good efficiency of the system in removing pollutants even in the case of using a unique column. Moreover, this system was determined to be able to meet the non potable reuse standards of water recycling in cities. The performance of the system in reducing chlorine demand was also drastic and results indicated a maximum of 66% and a minimum of 50% decrease in this regard.